Ecotourism and theories of learning/education - González Herrera, Manuel Ramón (Routledge. Taylor & Francis Group, 2021)
Ecotourism is a scientific discipline closely related to the processes of the foundation and development of tourism, which at the same time constitutes an academic discipline as this activity becomes an objective for teaching and learning. For this reason, it is necessary to know how to teach and communicate knowledge to students, and how students learn during this education process. The Ecotourism education category is understood in this chapter as the teaching and learning processes that take place in different institutions, whether formal or non-formal, schooled or out of school. This educational process has the characteristics of a theoretical system composed of concepts, categories, laws, and a particular structure of its components, which determines an internal logic, in which different external conditions to the object itself intervene. According to this theoretical position, this chapter presents six sections organized in this order: Ecotourism and Education, the Ecotourism education process, theoretical and methodological bases of the teaching and learning processes, theories of knowledge and psychoeducational paradigms applicable to Ecotourism, teaching opportunities applicable to Ecotourism Education, and models and teaching approaches applicable to Ecotourism education.